Supervision Management at the Education Area Coordinator of Waled District, Cirebon Regency - Agus Alif Humaydiy (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Supervision management in sub-district education area coordinators is an important process in efforts to improve the quality of education at the local level. Effective educational supervision can help improve the quality of learning, increase teacher competency, and improve student learning outcomes. This study aims to describe the role and practice of supervision management in sub-district education area coordinators and their impact on improving the quality of education.The research results show that good supervision management in sub-district educational area coordinators can increase the effectiveness of the learning process. Teachers and principals feel more supported in developing their skills, and this has a positive impact on improving student learning outcomes. Apart from that, efficient supervision management also facilitates collaboration between schools and related parties, such as local governments, to overcome education problems at the local level.In this context, management supervision in the sub-district education area coordinator plays a key role in improving the quality of education. Therefore, greater attention is needed to develop managerial and leadership skills for sub-district educational area coordinators, as well as strengthening cooperation between them, teachers and school principals to achieve better educational goals.